Evaluating the e-GP system in Local Government Institutions (LGIs): a study on 30 Pourashavas - Hossain, Jobaida (Brac University, 2022)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2019.